2020
DOI: 10.1186/s12984-020-00775-2
|View full text |Cite
|
Sign up to set email alerts
|

Postural control strategy after incomplete spinal cord injury: effect of sensory inputs on trunk–leg movement coordination

Abstract: Background Postural control is affected after incomplete spinal cord injury (iSCI) due to sensory and motor impairments. Any alteration in the availability of sensory information can challenge postural stability in this population and may lead to a variety of adaptive movement coordination patterns. Hence, identifying the underlying impairments and changes to movement coordination patterns is necessary for effective rehabilitation post-iSCI. This study aims to compare the postural control strategy between iSCI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…The cut-off frequency of the low-pass filter was chosen based on inspecting the IMU time series' magnitude spectra, with the meaningful frequency content (i.e., the frequency content associated with the motion of the participant) found between 0 and 5 Hz. In agreement with this, previous studies have shown that sway oscillations of standing balance contain frequencies between 0 and 5 Hz [28,29].…”
Section: Data Acquisitionsupporting
confidence: 89%
See 1 more Smart Citation
“…The cut-off frequency of the low-pass filter was chosen based on inspecting the IMU time series' magnitude spectra, with the meaningful frequency content (i.e., the frequency content associated with the motion of the participant) found between 0 and 5 Hz. In agreement with this, previous studies have shown that sway oscillations of standing balance contain frequencies between 0 and 5 Hz [28,29].…”
Section: Data Acquisitionsupporting
confidence: 89%
“…This result shows that a higher BBS total score at discharge could be attributed to better intersegment coordination. We previously have shown the high reliability of MSC in identifying balance impairments in different test conditions in patients with impaired balance [29]. We did not observe any significant Spearman's correlation between other balance biomarkers and BBS total score nor between each balance biomarker and each BBS task score at both admission and discharge test sessions (see online suppl.…”
Section: Imu-based Balance Biomarkers Versus Bbsmentioning
confidence: 66%
“…First, we measured the lower limb motion using only standardized angular velocity data. A previous study investigated the adaptation of the ankle and ankle-hip strategies based on the mean magnitude-squared coherence between the trunk-leg accelerations (Noamani et al, 2020 ). Another study measured the effect of co-contraction of the plantar and dorsiflexor muscles on the postural sway using a computational simulation study (Fok et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For individuals with SCI, a disruption in the flow of information below the level of injury impairs the ability to make muscle contractions and as a result, many systems of postural control are negatively affected ). During standing for example, individuals with SCI have been shown to have decreased limits of functional stability (Houston et al, 2020;Lemay et al, 2014), decreased movement coordination (Noamani et al, 2020), and increased postural sway (Lemay et al 2013).…”
Section: Postural Control In Scimentioning
confidence: 99%